2000
DOI: 10.1677/joe.0.1650271
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the acid-labile subunit of the insulin-like growth factor binding protein complex in human serum: a comparison of four immunoassays

Abstract: The acid-labile subunit (ALS) of the high molecular weight insulin-like growth factor binding protein complex is a liver-derived glycoprotein which is regulated by growth hormone and serves as a serum marker of growth hormone action. We have compared the measurement of ALS by four immunoassay methods (two RIAs, two ELISAs) utilizing various polyclonal and monoclonal antibodies raised against natural or recombinant human ALS, or synthetic ALS peptides. Despite the variety of methodologies and reagents, results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…However, this previous study in rats used a heterologous IGF-I RIA, which may have underestimated rat IGF-I levels. Interestingly, our estimates indicate a significant molar excess of IGFBP-3 to ALS before 4-8 weeks of age, which may be discordant with human data [26,36].…”
Section: Discussionsupporting
confidence: 55%
“…However, this previous study in rats used a heterologous IGF-I RIA, which may have underestimated rat IGF-I levels. Interestingly, our estimates indicate a significant molar excess of IGFBP-3 to ALS before 4-8 weeks of age, which may be discordant with human data [26,36].…”
Section: Discussionsupporting
confidence: 55%
“…However, this would apply equally to all ALS assays compared in this study and would therefore not explain differences between the methods of serum pre-treatment for ALS unfolding. In this study, we confirm the observation of other authors (1,4,10) that ALS levels are elevated in acromegaly. In contrast to Baxter's findings, we found that the usefulness of ALS quantification in the diagnosis of GH excess is dependent on the assay used for testing.…”
Section: Discussionsupporting
confidence: 93%
“…ALS concentrations in adults (1,4) and children (3,5,6) with GH deficiency (GHD) are lower than in normal controls; ALS increases with GH replacement therapy (3,7,8); and the change in ALS is highly correlated with the growth response in children (9). ALS is elevated in conditions of GH excess (4,10) and declines with successful treatment (11). The diagnostic accuracy of ALS using the commercially available SDS-ELISA in the diagnosis and follow-up of patients with acromegaly remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although IGFBP-3 determinations are comparatively less problematic and have several inherent advantages (4,13), the reported variable proteolysis of IGFBP-3 could adversely affect their detectability as different assays may recognize different IGFBP-3 variants (4,13,25). Although the potential value of the third member of the IGFBP-3 complex, ALS, have been long recognized (12), commercial ALS methods have only recently became available (11,26). This new development should encourage a more detailed evaluation of ALS physiology and its potential diagnostic applications.…”
mentioning
confidence: 99%